(untitled) (Journal of Asian Development Studies, 2025)
Urbanization has emerged as one of the most transformative processes shaping contemporary societies, fundamentally altering human settlement patterns, socioeconomic structures, and social interaction dynamics. The objective of this exploratory study was to synthesize critically the multidisciplinary literature to examine the evolution and characteristics of urbanization, the dynamics of social networks within urban settings, and the implications of urbanization on social interactions. It vividly demonstrates the urban spatial characteristics including population density, accessibility, transportation systems, public facilities, land-use diversity, and neighbourhood composition shape opportunities for mobility and the formation of both strong and weak social ties. While advances in transportation and digital communication have reduced the constraints of geographical distance, face-to-face interactions remain essential for strengthening social cohesion, community participation, employment opportunities, and psychological well-being. The synthesis further reveals that rapid urbanization simultaneously promotes economic growth, knowledge exchange, and social mobility while generating challenges such as social fragmentation, infrastructure deficits, housing shortages, environmental pressures, and widening social inequalities. The study contributes to urban theory by offering a comprehensive perspective on the complex relationships between urbanization and social interaction, with implications for developing inclusive, resilient, and socially connected cities.